Consonant length as expressive resource in sung Spanish - Guzmán, Mariano Nicolás (2018)
In classical singing, the pronunciation of Spanish is subordinated to an aesthetic canon which limits the expressive range of speech. According to this canon, vowels have a leading role since they can be sustained, while consonants must be articulated “clearly” but “marked”. Due to these requirements, consonants must be shortened in classical singing, which ignores their variability and identity effects on communication. In order to study the imposition of this aesthetic canon in classical singing and how they are articulated outside of that canon, we measured the length of the consonants /l m n/ (which can be sustained) in 10 famous singers’ recordings (5 classical and 5 folk) of “La Tempranera” by Carlos Guastavino. The correlation between syllable length and consonant length was significant in all cases, which indicates that the consonants /l m n/ keep in proportion with the subsequent vowels. The absolute and relative lengths were higher in folk-style performances (means = 0.109 s 27.61%) than in classical ones (means = 0.090 s 21.86%). Nevertheless, the data showed a high length variability in both singing styles. These results show that in Spanish folk singing the consonants /l m n/ in consonant-vowel syllables tend to be longer than in classical singing. However, although the imposed aesthetic canon seems to have an effect on the classical performances’ pronunciation, the evidence suggests that the length of the consonants /l m n/ is used in an expressive way in both singing styles.